Pyrrolopyrrole cyanine free radical photo-thermal material with high photo-thermal conversion efficiency as well as preparation method and application of pyrrolopyrrole cyanine free radical photo-thermal material

By designing the electron donor-acceptor type pyrrolopyrocyanine free radical photothermal material, the problem of the existing organic small molecule photothermal material is solved, and efficient photothermal conversion and excellent water evaporation are achieved. , thermal and electrical application performance.

CN119119051AActive Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411231664.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The light absorption range and low photothermal conversion efficiency of existing organic small molecule photothermal materials limit their application in the field of solar-driven water evaporation.

Method used

An electron donor-acceptor (D-A) type pyrrolopyrocyanine free radical photothermal material was designed. By introducing free radical structure, the energy band gap and absorption capacity of the molecule were enhanced, and obtained through specific preparation methods. The material, including chemical reactions using iron catalysts and phosphine compounds, form solid-state materials with wide absorption spectrum and high molar extinction coefficient.

Benefits of technology

It has achieved efficient photothermal conversion, with an interface water vapor efficiency of 98.6%, and has good performance in the integrated applications of thermoelectric, hydroelectric-thermal-thermal-electricity-energy-electricity driven by solar energy, with excellent photothermal conversion efficiency and stable thermoelectric output.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119051A_ABST
    Figure CN119119051A_ABST
Patent Text Reader

Abstract

The invention discloses a pyrrolopyrrole cyanine free radical photo-thermal material with high photo-thermal conversion efficiency as well as a preparation method and application of the pyrrolopyrrole cyanine free radical photo-thermal material. The synthesis method comprises the following synthesis steps: carrying out a reaction on a raw material TPA-CN and diisopropyl succinate to obtain a pyrrolo-pyrrole compound DPP-TPA, and further carrying out a condensation reaction on the pyrrolo-pyrrole compound DPP-TPA and 2-(5-tert-butylbenzoxazole) acetonitrile to obtain a compound H-PPCy-TPA. The H-PPCy-TPA can generate carbon free radicals, and the solid absorption peak edge can reach 1000 nm. Under the irradiation of one simulated sunlight (1 kW. M <-2 >), the water vapor efficiency of the interface water evaporation device based on H-PPCy-TPA1 / sponge is 98.6%, and the water evaporation rate is 1.435 kg.m <-2 >. H <-1 >; the H-PPCy-TPA1 is applied to an integrated device for thermal power generation, and the maximum voltage reaches 224 mV; the H-PPCy-TPA1 is used for a water and electricity integrated device, the water evaporation rate is 1.172 kg.m <-2 >. H <-1 >, and the maximum voltage reaches 180 mV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of organic small molecule photothermal materials, and relates to a pyrrolopyrrole cyanine free radical photothermal material with high photothermal conversion efficiency, and a preparation method and application thereof. Background Art

[0002] Solar energy is a green energy that is easily accessible, low-cost and high-value, and it occupies an important proportion in the development and utilization of new energy. Photothermal conversion technology, as the most direct method to utilize solar energy, has attracted the attention of researchers. Photothermal materials (also called photothermal conversion materials) are an important part of this technology. They convert the absorbed light energy into thermal energy. Common photothermal materials include metal nanomaterials, carbon-based materials, inorganic semiconductor materials, etc., but they have shortcomings such as high cost, difficulty in preparation, and limited light absorption capacity. In recent years, organic small molecule photothermal materials have been considered as a promising solar absorption material due to their structural diversity and adjustability, easy processing, and strong resistance to photobleaching. They have shown great application potential in solar-driven water evaporation and hydropower-heat and power cogeneration. However, the limited absorption range and low photothermal conversion efficiency limit the application of organic small molecule photothermal materials in the field of solar-driven water evaporation.

[0003] Introducing free radicals into organic small molecules to enhance the photothermal effect is an innovative strategy. Free radicals contain unpaired electrons, have a unique electronic structure, and reduce the energy band gap of the molecule, enhancing the absorption of light by the molecule, especially the absorption of near-infrared light. These properties play an important role in absorbing longer wavelengths and non-radiative transitions of excited states. At present, there are few reports on organic small molecule photothermal materials with free radicals. Summary of the invention

[0004] In view of the existing problems, the present invention designs an electron donor-acceptor (DA) type pyrrolopyrrole cyanine free radical photothermal material, the structural formula of which is as follows:

[0005]

[0006] Wherein, R is a diphenylamine unit and a triphenylamine unit, that is:

[0007]

[0008] This type of free radical photothermal material is an organic small molecule free radical molecule, which exhibits unique diradical properties and solid-state π-π stacking. The material is endowed with wide absorption spectrum characteristics through intramolecular charge transfer transitions and free radical characteristics. The large conjugated structure is beneficial to improving the molar extinction coefficient. In addition, the strong intermolecular π-π / H bond interaction and polyphenyl rotor units increase the probability of non-radiative transitions, which is beneficial to photothermal conversion.

[0009] At the same time, the present invention also provides the pyrrolopyrrole cyanine free radical photothermal material and a preparation method thereof, and the preparation process is as follows:

[0010]

[0011] The preparation method thereof comprises the following steps:

[0012] (1) Place small pieces of sodium in a reaction bottle, add tert-amyl alcohol, and add an iron catalyst under nitrogen protection. The iron catalyst can be FeCl3, Fe2(SO4)3, FeCl2, FeSO4, preferably FeCl3. Heat to 100-110°C, wait until the sodium is completely dissolved, add the raw material TPA-CN, the mass ratio of which to sodium is 1:2, and then add 0.5-1 equivalents of diisopropyl succinate. After the reaction is completed, cool and add an alcohol solvent. The alcohol solvent can be: methanol, ethanol, n-propanol, isopropanol, n-butanol, n-pentanol, preferably methanol. Precipitate a solid, filter, wash the solid with water, and dry to obtain the intermediate compound DPP-TPA.

[0013] (2) Add the intermediate DPP-TPA and 1-2 equivalents of 2-(5-tert-butylbenzoxazole)acetonitrile to a reaction flask, add a high boiling point solvent, which includes toluene, chlorobenzene, o-dichlorobenzene, dimethylformamide, xylene, diphenyl ether, preferably toluene, and heat to 70-90° C. under nitrogen protection, and then add 7-8 equivalents of a phosphine compound, which includes PCl3, PCl5, POCl3, preferably POCl3. Continue heating to 140-170° C., stop the reaction after 0.5-2 hours, cool to room temperature, add methanol to precipitate a solid, and purify by recrystallization to obtain the compound H-PPCy-TPA.

[0014] In addition, the pyrrolopyrrole cyanine free radical photothermal material provided by the present invention is used in the fields of water evaporation, thermal power generation and hydrothermal integration. –2 ) irradiation, the water vapor efficiency of the interfacial water evaporation device based on H-PPCy-TPA1 / sponge was 98.6%, and the water evaporation rate was 1.435 kg.m –2 .h –1 ; When H-PPCy-TPA1 is used in an integrated device for thermal power generation, the maximum voltage reaches 224mV; When H-PPCy-TPA1 is used in a hydroelectric integrated device, the water evaporation rate is 1.172kg.m –2 .h –1 and the maximum voltage reaches 180mV. This technology provides guidance for the rational design of high-performance organic photothermal materials and an effective technical approach for efficient interfacial water evaporation.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] (1) The pyrrolopyrrole cyanine free radical photothermal material of the present invention has the characteristics of absorption in the near-infrared region in the solution state, high molar extinction coefficient, and wide spectrum absorption in the solid state.

[0017] (2) The pyrrolopyrrole cyanine free radical photothermal material of the present invention has excellent photothermal conversion efficiency, and the water vapor efficiency of the interfacial water evaporation device is as high as 98.6%. At the same time, it has good application prospects in solar-driven thermoelectricity and hydropower-thermoelectric integration. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the time-of-flight mass spectrum of H-PPCy-TPA1 prepared in Example 1.

[0019] Figure 2 This is the single crystal structure of H-PPCy-TPA1 prepared in Example 1.

[0020] Figure 3 Time-of-flight mass spectrum of H-PPCy-TPA2 prepared in Example 2

[0021] Figure 4 This is the UV-visible absorption spectra of H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2 in dichloromethane.

[0022] Figure 5 UV-visible absorption spectra of the solid powders of H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2.

[0023] Figure 6 The electron paramagnetic resonance spectra of H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2.

[0024] Figure 7 H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2 were heated to 0.8 w cm -2 On-off cycle curve under 808nm laser irradiation.

[0025] Figure 8 This is a graph of the water evaporation rate of H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2 under one sun.

[0026] Fig. 9 The voltage diagram of the H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2 under the irradiation of one sun.

[0027] Fig.10This is a graph of the water evaporation rate of H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2 in a hydropower integrated application under solar irradiation.

[0028] Fig.11 Voltage diagram of H-PPCy-TPA1 and H-PPCy-TPA2 prepared in Examples 1 and 2 in a hydropower integrated application under sunlight. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is further described below in conjunction with embodiments, but the scope of protection claimed by the present invention is not limited to the scope described in the embodiments.

[0030] Embodiment 1

[0031] (1) 4-(Diphenylamino)benzaldehyde (5 g, 19.29 mmol) and 50 mL of tetrahydrofuran were added to a round-bottom flask, and iodine (9.285 g, 36.58 mmol) was added after stirring to dissolve, followed by 250 mL of aqueous ammonia. The flask was sealed and reacted at room temperature for 12 h. After the reaction was completed, sodium thiosulfate was added and the mixture was stirred until the solution became clear. The tetrahydrofuran was removed by rotary evaporation under reduced pressure, and the resulting solution was transferred to a separatory funnel and extracted with dichloromethane and water. The organic layers were combined, dried over anhydrous sodium sulfate, and filtered. The crude product was purified by column chromatography to obtain a light yellow solid raw material TPA-CN1 (4.45 g) with a yield of 90%.

[0032]

[0033] (2) Sodium (0.510 g, 0.022 mol) was cut into pieces the size of soybeans and placed in a 150 mL round-bottom flask. 15 mL of tert-amyl alcohol was added to the flask, and then anhydrous ferric chloride (catalytic amount) was added under the protection of nitrogen. The mixture was heated to 110° C. After the sodium was completely dissolved, compound TPA-CN1 (3 g, 0.085 mol) was added. Subsequently, diisopropyl succinate (1.122 g, 0.0425 mol) was added dropwise. The reaction was stopped after 5 hours of reaction. After the reaction solution was cooled, a large amount of methanol was added to precipitate solids. The solids were then filtered under reduced pressure, and the filter cake was washed with methanol and water until the filtrate was clear. The filter cake was collected and dried to obtain brown solid DPP-TPA1 (1.85 g) with a yield of 35%.

[0034]

[0035] (3) DPP-TPA1 (642 mg, 1.032 mmol), 2-(5-tert-butylbenzoxazole)acetonitrile (773 mg, 3.614 mmol) and 20 mL of anhydrous o-dichlorobenzene were added to a round-bottom flask. The mixture was heated to 90°C under nitrogen protection, followed by the addition of POCl3 (1.266 g, 8.258 mmol) and then heated to 140°C. The reaction was stopped after 30 minutes of reaction, the reaction solution was cooled to room temperature, and methanol was added to precipitate the solid to obtain a crude solid. The crude product was purified by recrystallization from a mixture of methanol and dichloromethane to finally obtain a purple solid H-PPCy-TPA1 (209 mg) with a yield of 20%.

[0036] Time-of-flight mass spectrum and single crystal structure of H-PPCy-TPA1 are shown in Figure 1 and Figure 2 MALDI-TOF (%): Calcd for C 68 H 54 N8O2[M+H] + 1015.4370, found 1015.0289.

[0037]

[0038] Embodiment 2

[0039] (1) 4-bromobenzonitrile (3 g, 0.0165 mol), 4-(diphenylamino)phenylboronic acid (6.187 g, 0.0214 mol) and potassium carbonate (22.778 g, 0.1648 mol) were added to a round-bottom flask. 20 ml of a mixed solvent of toluene / methanol / water with a volume ratio of 3:1:1 was added, and tetrakis(triphenylphosphine)palladium (catalytic amount) was added under the protection of nitrogen, heated to 90°C and stirred for 12 hours. After the reaction was completed, it was extracted with dichloromethane and the organic layers were combined. The crude product was purified by column chromatography to obtain a light yellow solid raw material TPA-CN2 (5.14 g) with a yield of 90%.

[0040]

[0041] (2) Sodium (0.398 g, 0.0173 mol) was cut into pieces the size of soybeans and placed in a 150 mL double-necked round-bottom flask. 15 mL of tert-amyl alcohol was added to the flask, and then anhydrous ferric chloride (catalytic amount) was added under the protection of nitrogen. The mixture was heated to 110°C, and after the sodium was completely dissolved, compound TPA-CN-2 (2.990 g, 0.087 mol) was added. Subsequently, diisopropyl succinate (0.875 g, 0.0433 mol) was added dropwise. The reaction was stopped after 5 hours of reaction, and after the reaction solution was cooled, a large amount of methanol was added to precipitate the solid. The solid was then filtered under reduced pressure, and the filter cake was washed with methanol and water until the filtrate was clear. The filter cake was collected and dried to obtain a brown-black solid DPP-TPA2 (4.088 g) with a yield of 61%.

[0042]

[0043] (3) DPP-TPA2 (1.599 g, 2.064 mmol), 2-(5-tert-butylbenzoxazole)acetonitrile (1.548 g, 7.228 mmol) and 50 mL of anhydrous o-dichlorobenzene were added to a round-bottom flask, and the mixture was heated to 90°C under nitrogen protection, followed by the addition of POCl3 (2.532 g, 16.516 mmol), and then heated to 140°C. The reaction was stopped after 30 minutes of reaction. The reaction solution was cooled to room temperature, and methanol was added to precipitate the solid to obtain a crude solid. The crude product was purified by recrystallization from a mixture of methanol and dichloromethane to obtain a purple solid H-PPCy-TPA2 (602 mg) with a yield of 25%.

[0044] The time-of-flight mass spectrum of H-PPCy-TPA2 is shown in Figure 3 MALDI-TOF (%): Calcd for C 80 H 62 N8O2[M+H] + 1166.4996, found 1166.9623.

[0045]

[0046] Performance test and application examples

[0047] Select a 1 cm wide quartz cuvette and add 2 mL of 10 -5 M of H-PPCy-TPA1, H-PCy-TPA2 in dichloromethane solution, and tested the UV-visible absorption spectrum, such as Figure 4As shown in the figure, the maximum absorption peak positions of H-PPCy-TPA1 and H-PPCy-TPA2 are 736 and 724 nm, respectively, which belong to near-infrared absorption. In addition, the solid powders of H-PPCy-TPA1 and H-PCy-TPA2 have broad absorption, and the absorption edge reaches 1000 nm, as shown in the figure. Figure 5 shown.

[0048] 20 mg of solid powder of H-PPCy-TPA1 and H-PPCy-TPA2 were taken for electron paramagnetic resonance test, and there were obvious carbon free radical signals, and the g values ​​were both 2.003. Among them, the free radical signal of H-PPCy-TPA1 was stronger than that of H-PPCy-TPA2, such as Figure 6 shown.

[0049] At 0.8W.cm -2 The 808nm laser was used as the light source to irradiate the solid powders of H-PPCy-TPA1 and H-PPCy-TPA2. The temperature of H-PPCy-TPA1 rose to 235℃ within 25s, and the temperature of H-PPCy-TPA2 rose to 226℃ within 25s. After ten cycles of switching laser, both molecules had good cyclic thermal stability, such as Figure 7 shown.

[0050] Preparation of water evaporation device: First, H-PPCy-TPA1 and H-PPCy-TPA2 were dissolved in dichloromethane, and a round sponge with a diameter of 2 cm was taken, and the lower part of the sponge was immersed in the solution and dried to obtain a sponge loaded with H-PPCy-TPA1 and H-PPCy-TPA2. The sponge was floated on the surface of water in a beaker to build a water evaporation device.

[0051] Water evaporation: Use a xenon lamp as a light source to simulate sunlight, and irradiate the sponge in the water evaporation device at a certain sunlight intensity; at the same time, use an analytical balance to detect the change in the water mass in the beaker. Figure 8 As shown in Figure 2, the water evaporation rate of H-PPCy-TPA1 reached 1.435 kg.m within 1 hour. -2 The water evaporation efficiency is 98.6%, and the water evaporation rate of H-PPCy-TPA2 reaches 1.185kg.m -2 , the water evaporation efficiency is 81.2%, indicating that H-PPCy-TPA1 and H-PPCy-TPA2 have excellent interfacial water evaporation capabilities.

[0052] Preparation of power generation device: First, H-PPCy-TPA1 and H-PPCy-TPA2 were dissolved in dichloromethane, and conductive glue was added and stirred evenly. The mixture was dripped onto the TEC1-12706 power generation sheet with a specification of 40mm×40mm×3.6mm using a test tube. The power generation sheet was glued to the heat dissipation sponge and floated on the surface of the water in the beaker to build a power generation device.

[0053] Voltage changes: Use a xenon lamp as a simulated sunlight source, illuminate the generator under a certain sunlight intensity, and use a multimeter to record the generated voltage. Fig. 9 As shown, the output voltage of H-PPCy-TPA1 after irradiation for 1 minute was 224 mV, and the output voltage of H-PPCy-TPA2 was 205 mV, indicating that the two molecules have excellent thermoelectric conversion capabilities.

[0054] Construction of a hydropower integrated device: Place the TEC1-12706 power generation sheet loaded with H-PPCy-TPA1 and H-PPCy-TPA2 on the surface of water floating in a beaker, and place the entire beaker on an analytical balance to build a hydropower integrated device.

[0055] Use a xenon lamp to simulate sunlight, irradiate the device at a light intensity of 1 sun, and use an analytical balance to detect the change in the water mass in the beaker, and use a multimeter to record the voltage generated. Fig.10 and Fig.11 As shown in the figure, after 1 hour of illumination, the water evaporation rate of H-PPCy-TPA1 in the thermoelectric integrated device reached 1.324 kg.m -2 , the water evaporation efficiency is 91.2%, and the output voltage is 179mV. The water evaporation rate of H-PPCy-TPA2 is 1.158kg.m -2 , the water evaporation efficiency is 79.3%, and the voltage can be outputted at 166mV. This shows that H-PPCy-TPA1 and H-PPCy-TPA2 have excellent water evaporation capacity in hydropower integration applications, and the waste heat generated can be used to output voltage, which can achieve full utilization of energy.

[0056] The above descriptions are only preferred embodiments of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A pyrrolopyrrole cyanine free radical photothermal material with high photothermal conversion efficiency, characterized in that: The chemical structure is: The structure of R is:

2. The method for preparing the pyrrolopyrrole cyanine free radical photothermal material according to claim 1, characterized in that The reaction process is as follows:

3. The method for preparing the pyrrolopyrrole cyanine free radical photothermal material according to claim 2, characterized in that: The steps include: (1) Put small pieces of sodium into a reaction bottle, add tert-amyl alcohol, add iron catalyst under nitrogen protection, heat to 100-110°C, wait until the sodium is completely dissolved, add raw material TPA-CN, the mass ratio of which to sodium is 1:2, and then add 0.5-1 equivalent of diisopropyl succinate. After the reaction is completed, cool, add alcohol solvent, precipitate solid, filter, wash the solid with water, and dry to obtain the intermediate compound DPP-TPA. (2) The intermediate DPP-TPA and 1-2 equivalents of 2-(5-tert-butylbenzoxazole)acetonitrile are added to a reaction flask, a high boiling point solvent is added, nitrogen protection is applied, the mixture is heated to 70-90°C, 7-8 equivalents of a phosphine compound are added, and the mixture is heated to 140-170°C. The reaction is stopped after 0.5-2 hours, the mixture is cooled to room temperature, methanol is added to precipitate a solid, and the solid is purified by recrystallization to obtain the compound H-PPCy-TPA.

4. The method for preparing the pyrrolopyrrole cyanine free radical photothermal material according to claim 3, wherein the iron catalyst in step (1) is FeCl3, Fe2(SO4)3, FeCl2, or FeSO4.

5. The method for preparing the pyrrolopyrrole cyanine free radical photothermal material according to claim 3, wherein the alcohol solvent in step (1) is: methanol, ethanol, n-propanol, isopropanol, n-butanol, or n-pentanol.

6. The method for preparing a pyrrolopyrrole cyanine free radical photothermal material according to claim 3, wherein the high boiling point solvent in step (2) comprises toluene, chlorobenzene, o-dichlorobenzene, dimethylformamide, xylene, or diphenyl ether.

7. The method for preparing pyrrolopyrrole cyanine free radical photothermal material according to claim 3, wherein the phosphine compound in step (2) is: PCl3, PCl5, POCl3.

8. The use of the pyrrolopyrrole cyanine free radical photothermal material according to claim 1, the water vapor efficiency of the water evaporation device is 98.6%, and the water evaporation rate is 1.435 kg.m -2 .h -1 ; Integrated device for thermal power generation, with a maximum voltage of 224mV; Integrated device for hydropower generation, with a water evaporation rate of 1.172kg.m -2 .h -1 and maximum voltage up to 180mV.

Citation Information

Patent Citations

  • Composition, film, near-infrared cutoff filter, laminate, pattern formation method, solid-state image sensor, image display device, infrared sensor and color filter

    CN108474884A

  • Pyrrolo-pyrrolo-cyanine compound with aggregation-induced emission and near-infrared emission fluorescent dye and preparation method of pyrrolo-pyrrolo-cyanine compound

    CN114656493A

  • Near-infrared emission asymmetric structure fluorine-boron fluorescent dye and preparation method thereof

    CN118184685A

  • Powdered dye composition, method for producing powdered dye composition, resin composition, and molded article

    CN118434822A

  • Resin composition and molded article

    US20160200970A1

Cited By

  • D-A-D type alpha-cyano pyrrolopyrrole photo-thermal material as well as preparation method and application thereof

    CN122502376A

  • A DAD-type α-cyanopyrrolopyrrole photothermal material, its preparation method and application

    CN122502376B